Law and the " Sharing Economy" : Regulating nline Market Platforms - Derek McKee (University of Otawa Press, 2018)
This fantastic collection about how our daily lives are changing with the rie of digital platforms brings together top legal scholars from around the world who offer invaluable insights on the full range of legal issues,from labour law to municipal law, information law to competition law,policymakers and regulators must confront in this new era.